FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PELANGGAN RUMAH MAKAN DI KOTA ENDE - Oy, Ermelinda Azi; Penu, Yustina Paulina (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
This study aims to determine the effect of food quality on restaurant customer loyalty. 2. To determine the effect of price on restaurant customer loyalty. 3. To determine the effect of promotion on restaurant customer loyalty. The research method used is a quantitative and qualitative approach method. This research was conducted in Ende City. The sample in this study was 100 restaurant customers in Ende City. This study uses Multiple Linear Regression analysis tools. The results of the analysis are as follows: The food quality variable shows that partially or individually it has a significant effect on customer loyalty of restaurants in Ende City with a significance level of 0.000 <0.05, and Tcount <Ttable (7.425> 1.660), The price variable shows that partially or individually it has a significant effect on customer loyalty of restaurants in Ende City. With a significance level of 0.000 <0.05, and Tcount> Ttable (8.346> 1.660). The promotion variable shows that partially or individually it has a significant effect on customer loyalty of restaurants in Ende City. With a significance level of 0.000 <0.05, and Tcount> Ttable (11.469> 1.660). The variables of food quality, price, promotion simultaneously or together have an effect on customer loyalty of restaurants in Ende City. The contribution of the food quality, price and promotion variables is 81.6% while the remaining 18.4% is explained by other variables that are not examined in this research model.